Putting Knowledge into Practice-The Challenge of Acquiring Healthy Habits during Pregnancy Colocando conhecimento em prática - O desafio de adquirir hábitos saudáveis durante a gravidez - Ana Carolina Godoy-Miranda; Jessica Fernandes Cirelli; Maira Pinho-Pompeu; Daiane Sofia Morais Paulino; Sirlei Siani Morais; Fernanda Garanhani Surita
Abstract Objective The aim of this study was to investigate the knowledge concerning gestational weight gain (GWG), nutrition, and physical exercise (PE) in pregnant women, and how to put them into practice. Methods A cross-sectional study with 61 pregnant women above 26 weeks of gestation, at the Woman's Hospital, CAISM, University of Campinas. Questionnaires regarding the knowledge of healthy habits (HH) during pregnancy, sociodemographic data, and previous obstetric outcomes were applied. An educational guide with advice on HH during pregnancy and in the postpartum period was offered. Results The average age of women was 28.7 ± 6.23 years, with 85% of them being married; 32% nulliparous; the average body mass index (BMI) before pregnancy was 25.4 ± 9.8 kg/m2, and themean number of years of schoolingwas 11.2 ± 3.8. Only 61%of the subjects had received any previous information about GWG during their antenatal care and were aware as to howmany pounds they should gain during pregnancy. Among the 61 women, 85% understood that they did not need to "eat for 2" and 99% knew that PE had benefits for their body and was safe for their baby. Half of the women practiced PE prior to pregnancy; however, only 31% continued the practice of PE during the pregnancy. Conclusion Despite understanding the need for HH during pregnancy, women still need encouragement to practice PE during pregnancy, as well as more information about GWG.